Using TiO2 Mesoflower Interlayer in Tubular Porous Titanium Membranes for Enhanced Electrocatalytic Filtration - Li, Xinyang; Liu, Guicheng; Shi, Mei; Li, Jiao; Li, Juan; Guo, Caiyang; Lee, Joong Kee; Zheng, Jianzhong (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
The current study focuses on synthesis and characterization of novel functionalized anodic membranes for wastewater treatment. This membrane was prepared by first constructing a TiO2 mesoflower interlayer on a tubular porous titanium membrane and subsequently coating an antimony-doped tin oxide catalytic layer. Physical and electrochemical characterizations of the membranes were evaluated. With TiO2 mesoflower, the membrane anode obtained a higher oxygen evolution potential, 2.22 V (vs saturated calomel electrode), relative roughness factor (701.7), and electrochemical porosity (99.23%) than membrane anodes without TiO2 mesoflower. The prepared membrane anode also achieved a low charge-transfer (0.11 V) and mass-transfer resistance (0.21 V) in filtration mode. The unique features were found linked to its 3-D porous and open structure, and formation of a Ti0.2Sn0.8O2 sosoloid that had a high surface oxygen (O-ad) content. The electrocatalytic filtration performance of this membrane was also tested using methyl orange as a model organic pollutant. At a current density of 15 mA cm(-2), the membrane achieved a higher 71.0% removal of methyl orange than 58.0% for the membrane without TiO2 mesoflower. At a 58.0% removal of methyl orange, the membrane consumed a much lower energy of 0.20 kWh m(-3) than 5.88 kWh m(-3) for membrane anodes without TiO2 mesoflower. The synthesized membrane electrode filter shows promise for future applications aimed to remove organic pollutants from wastewater. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: CARBON NANOTUBE NETWORK; WASTE-WATER TREATMENT; ELECTROCHEMICAL OXIDATION; ORGANIC POLLUTANTS; ELECTRODE; ANODE; REACTOR; ELECTROOXIDATION; DEGRADATION; PERFORMANCE